Débat - Caldwell, Gary; Bélanger, Gérard; Dumont, Fernand; Tremblay, Marc-Adélard; Langlois, Simon; Desaulniers, Jean-Pierre; Fournier, Marcel; Gagnon, Gabriel; Desaulniers, Jean-Pierre; Dumont, Fernand; Desaulnliers, Jean-Paul; Dumont, Fernand; et al. (Recherches sociographiques)

(untitled) (Département de sociologie, Faculté des sciences sociales, Université Laval, 1985)
Débat